Development and Validation of Stability-Indicating RP-UPLC Method for the Determination of Methdilazine in Bulk Drug and in Pharmaceutical Dosage Form. (31st October 2012) - Raghu, Madihalli S.; Basavaiah, Kanakapura; Xavier, Cijo M.; Prashanth, Kudige N.
Abstract : A simple, precise, and accurate, and stability-indicating isocratic Ultraperformance Liquid Chromatography (UPLC) method was developed for the determination of methdilazine hydrochloride (MDH) in bulk drug and in its tablets. The use of UPLC, with a rapid 5-minute-reversed-phase isocratic separation on a 1.7 μ m reversed-phase packing material to provide rapid ''high throughput'' support for MDH, is demonstrated. The method was developed using Waters Acquity BEH C18 column (100 mm × 2.1 mm, 1.7 μ m) with mobile phase consisting of a mixture of potassium dihydrogenorthophosphate and 1-pentane sulphonic acid buffer of pH 4.0 and acetonitrile (60 : 40 v/v). The eluted compound was detected at 254 nm with a UV detector. The standard curve of mean peak area versus concentration showed an excellent linearity over a concentration range 0.5–80 μ g mL −1 MDH with regression coefficient (r ) value of 0.9999. The limit of detection (S / N = 3 ) was 0.2 μ g mL −1 and the limit of quantification (S / N = 10 ) was 0.5 μ g mL −1 . Forced degradation of the bulk sample was conducted in accordance with the ICH guidelines. Acidic, basic, hydrolytic, oxidative, thermal, and photolytic degradations were used to assess the stability indicating power of the method. The drug was found to be stable in acidic, basic, thermal, hydrolytic, and photolytic stress conditions and showed slight degradation in oxidative stress condition.